STUDI IN SILICO SENYAWA TUMBUHAN FAMILI ASTERACEAE SEBAGAI PENGHAMBAT ENZIM XANTIN OXIDASE - Oky Hermansyah; Fadila Jeni Salsabila; Reza Pertiwi; Riana Versita; Ikhsan Ikhsan (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Asteraceae family plants contain flavonoid and phenolic compounds which have many benefits including inhibiting the xanthine oxidase enzyme, this enzyme plays a role in the conversion of purines into uric acid. Excessive production of uric acid in the body can cause deposition in the joints which causes pain and stiffness and swelling of the joints. Inhibition of this enzyme can normalize the amount of uric acid in the body and reduce its effects. This study aims to determine the potential of Asteraceae family plants with the best inhibition of the xanthine oxidase enzyme using the in silico method with molecular docking. The potential of the compound was assessed based on the parameters of bond energy values, inhibition constants, hydrogen bonds and amino acid residues. The size of the molecular docking center in this study x= 95,226; y= 47,251; z = 112,78 with volume x, y, and z = 40. The simulation results show that the test compound that has the best bond energy value (ΔG) is myrisetin of -10.58 kCal/mol. In general, from the research results, myrisetin compounds contained in the asteraceae family of chrysanthemum plants are compounds that have the potential to be further tested in vitro or in vivo as inhibitors of the xanthine oxidase enzyme.